Assessment of Non-Government Organizationsa Contribution to Environmental Awareness in Nigeria (Global Journal of Human-Social Science, 2012)
Environmental management challenges have assumed a global scale and attention However it is misleading to conclude that the current challenge of sustainable environmental management is fully known to the populace especially at the grassroots This paper examined Non-Government Organizations Contribution to Environmental Awareness in Nigeria using Uyo as a case study The study collected data using the semi-structured questionnaire on awareness of environmental issues relationship between people in the study area and ENGOs activities of ENGOs and benefits from ENGOs Findings revealed that ENGOs has not significantly created a positive environmental awareness on respondents and has consequently failed to meet global expectations in addressing environmental challenges Recommendations were made to enhance environmental awareness improved education and orientation of the people on environmental problems encouragement of youth participation in environmental management by ENGOs media houses should increase awareness of environmental problems in the study area and funding agencies should monitor the implementation of planned environmental awareness programmes
Keywords: ENGOs; Environmental awareness; Environmental problems; Environmental management; Uyo